Multimodal Learning Strategies in Secondary EFL Education: Insights from Teachers - Rohi, Maria Paulina; Nurhayati, Lusi (Universitas Hamzanwadi, 2024)
Multimodal learning has shown promise in various educational settings, positively impacting teaching and learning outcomes. However, the multifaceted effects of multimodal learning on secondary EFL students' second language acquisition still need to be explored, especially at the secondary school level. A deeper understanding of how multimodal learning—which involves the integration of linguistic, auditory, visual, and kinesthetic modalities to convey information—influences second language learning is crucial for effective language teaching. The study aims to explore the role and instructional practices of multimodal learning in enhancing students' second language outcomes through in-depth interviews with teachers. Eight English teachers from several junior high schools across East Nusa Tenggara, Indonesia, participated in the study. The participants had varied teaching experiences: three teachers with 6–10 years, four with 11–15 years, and one with over 16 years of experience. The results indicate that teachers have diverse experiences integrating various combinations of learning modes into their teaching practices. Four key themes emerged regarding the role of multimodal learning in students' second language acquisition, enhancing understanding, improving retention, encouraging participation and motivation, and accommodating different learning styles. This study offers insights for teachers to optimize their teaching strategies and highlights the effectiveness of multimodal approaches in English language education.